Comparative analysis of slow pyrolysis of sugarcane bagasse and corn stover for renewable energy production - Abuelnuor A. A. Abuelnuor; Mohamed Ali Abuelnour; O. S. Abd El-Kawi (Discover Energy)
Abstract This study presents a comparative analysis of slow pyrolysis applied to sugarcane bagasse from the Kenana Factory in Sudan and corn stover, focusing on biofuel production potential. Experiments were conducted with a heating rate of 0.9 °C/s, raising temperatures from 255 °C to 686 °C over a 50-min residence time. The results show that corn stover achieved a higher bio-oil yield (5.3%) than bagasse (4.26%) and a combined mixture (6.3%). Biochar yields were highest for the bagasse-corn stover mixture at 64.4%. Notably, the calorific value of biochar from corn stover reached 40.8 MJ/kg compared to 38.8 MJ/kg for bagasse, indicating its greater potential for energy applications. These findings underscore the suitability of Sudanese agricultural residues for renewable energy, with corn stover emerging as a favorable bio-oil and biochar source.